Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Reality Therapy on Reducing Anxiety in Mothers of Children with Autism - Changizi, Akram; Mohammadi, Akbar (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to compare the effectiveness of Cognitive-Behavioral Therapy (CBT) and Reality Therapy in reducing anxiety in mothers of children with autism in Shahriar County. Methods and Materials: The research design was a quasi-experimental type with a pre-test and post-test control group. The statistical population included 30 mothers of children with autism whose children were enrolled in one of the exceptional schools in Shahriar County during the 2023-2024 academic year. The sample consisted of 30 mothers selected using convenience sampling and divided into two experimental groups (15 each) and a control group (15). The Beck Anxiety Inventory (1988) was used as the measurement tool. Data were analyzed using covariance analysis. Findings: The results indicated that both Cognitive-Behavioral Therapy and Reality Therapy were effective in reducing anxiety in mothers of children with autism. However, Reality Therapy had a greater impact on reducing anxiety compared to Cognitive-Behavioral Therapy (P < 0.01). Conclusion: Both Cognitive-Behavioral Therapy and Reality Therapy can effectively reduce anxiety in mothers of children with autism, with Reality Therapy showing a greater impact.